2008
DOI: 10.1071/ea07407
|View full text |Cite
|
Sign up to set email alerts
|

Higher weaning weight improves postweaning growth and survival in young Merino sheep

Abstract: Two monitoring projects were conducted to investigate weaner mortality in commercial Merino flocks in the Yass and the Central Tablelands Rural Lands Protection Boards located in the Southern Tablelands agricultural region of New South Wales. The projects were conducted in Yass in 2005 and in the Central Tablelands in 2006. A random sample of weaners from four flocks in the Yass board and 11 flocks in the Central Tablelands board were regularly weighed, growth rates were calculated after weaning and survival w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
5
13
0
Order By: Relevance
“…Progeny that were heavier at weaning remained heavier during the first summer and autumn when most deaths occurred and had higher survival rates to 12 months of age than those that were lighter at weaning. This is consistent with the findings of Denney (1990), Hatcher et al (2008) and Campbell et al (2009) and occurred despite evidence of compensatory growth by the lighter weaners. Survival rates were very sensitive to liveweight when weaning weight was below 20 kg, whereas the changes in weaner survival from increasing weaning weights above 20 kg were much smaller.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Progeny that were heavier at weaning remained heavier during the first summer and autumn when most deaths occurred and had higher survival rates to 12 months of age than those that were lighter at weaning. This is consistent with the findings of Denney (1990), Hatcher et al (2008) and Campbell et al (2009) and occurred despite evidence of compensatory growth by the lighter weaners. Survival rates were very sensitive to liveweight when weaning weight was below 20 kg, whereas the changes in weaner survival from increasing weaning weights above 20 kg were much smaller.…”
Section: Discussionsupporting
confidence: 81%
“…Most weaner mortalities occurred during the 5 months after weaning, which is consistent with the findings of Hatcher et al (2008) and Campbell et al (2009). The average growth rate during this period for weaners from different pre-weaning nutritional treatments was not significantly associated with mortality risk of individual progeny at either site.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These correlations were only different from zero for Texel, Ile de France, German Mutton Merino and German Blackheaded. Weaning weight is the most important factor in determining postweaning liveweight, growth rates and survival of Merino lambs (Hatcher, 2008). This positive relationship was also proved in this study, except for the German Blackheaded.…”
Section: Genetic Correlationsmentioning
confidence: 99%
“…The ability of the lamb to undergo compensatory growth postweaning has been demonstrated by Hatcher et al (2008). Similarly, Galvani et al (2014) reported that lambs reared by low milk yielding ewes had the greatest DMI and subsequently growth rate throughout the postweaning period.…”
Section: Discussionmentioning
confidence: 93%